A modified Tet‐ON system minimizing leaky expression for cell‐type specific gene induction in medaka fish. (26th August 2021) - Hosoya, Osamu; Chung, Myung; Ansai, Satoshi; Takeuchi, Hideaki; Miyaji, Mary
Abstract: The Tet‐ON system is an important molecular tool for temporally and spatially‐controlled inducible gene expression. Here, we developed a Tet‐ON system to induce transgene expression specifically in the rod photoreceptors of medaka fish. Our modified reverse tetracycline‐controlled transcriptional transactivator (rtTAm) with 5 amino acid substitutions dramatically improved the leakiness of the transgene in medaka fish. We generated a transgenic line carrying a self‐reporting vector with the rtTAm gene driven by the Xenopus rhodopsin promoter and a tetracycline response element (TRE) followed by the green fluorescent protein (GFP) gene. We demonstrated that GFP fluorescence was restricted to the rod photoreceptors in the presence of doxycycline in larval fish (9 days post‐fertilization). The GFP fluorescence intensity was enhanced with longer durations of doxycycline treatment up to 72 h and in a dose‐dependent manner (5–45 μg/ml). These findings demonstrate that the Tet‐ON system using rtTAm allows for spatiotemporal control of transgene expression, at least in the rod photoreceptors, in medaka fish. Abstract : We developed a TetON system by using a mutated transcriptional transactivator.